Intra-rater reliability and validity of navicular drop test for the assessment of medial longitudinal arch in patients having pronated feet with chronic low back pain - Md Farhan Alam; Saima Zaki; Saurabh Sharma; Mohammed Ghareeb; Shibili Nuhmani (Clinical Epidemiology and Global Health)
Background: The Navicular Drop (ND) test serves as a diagnostic tool for evaluating foot protonation by measuring the variation in the height of the navicular tuberosity between sitting and standing positions. Pronated feet (PF) are considered to be associated with lower limb injuries and low back pain (LBP). Hence, a highly reliable assessment method for accurately diagnosing foot protonation is essential. Purpose: This study aimed to explore the intra-rater test-retest reliability, Standard Error of Measurement (SEM), Smallest Detectable Difference (SDD) and validity related to the ND test among patients having PF with chronic low back pain (CLBP). Methods: Foot protonation was measured using the ND test for both lower limbs on a sample of 45 CLBP patients (16 male, 29 female). Intraclass correlation coefficients (ICC), SEM and SDD values were calculated to obtain reliability and measurement error. Results: The test-retest reliability of the ND test was found to be good, exhibiting ICC values of 0.89 for the dominant limb and 0.82 for the non-dominant limb. The 95 % confidence intervals (CI) were reported as 0.804 to 0.941 for the dominant limb and 0.672 to 0.901 for the non-dominant limb. The SEM and SDD were 0.94 and 2.62 for the dominant limb, and 1.35 and 3.75 for the non-dominant limb, respectively. Conclusion: The findings of the study suggested ND test is a reliable method for measuring foot arches, making it applicable in clinical practice to assess patients for foot protonation.